2022
DOI: 10.1093/arclin/acac003
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of the African Neuropsychology Battery in Persons of African Descent

Abstract: Objective The African Neuropsychology Battery (ANB) includes eight culturally appropriate cognitive tests developed for use in the Congo and other sub-Saharan African populations. The current study examines the reliability of the ANB in three samples of participants of African descent. Methods Subjects were recruited in the United States and the Congo to participate in three studies of ANB internal consistency reliability (St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Factors linking migration and cognitive outcomes are complex and, in most cases, multidimensional, impacting initial levels of cognitive function and the rate of cognitive changes over time (Xu, Dupre, et al, 2019). For example, Ikanga et al, in press) tested a core assumption of the African Neuropsychology Battery (ANB), according to which greater African enculturation is associated with better performance on the ANB. The ANB assesses visuospatial perception, naming, memory, and abstract reasoning based on content drawn from sub-Saharan African cultures.…”
Section: Aims Of This Reviewmentioning
confidence: 99%
“…Factors linking migration and cognitive outcomes are complex and, in most cases, multidimensional, impacting initial levels of cognitive function and the rate of cognitive changes over time (Xu, Dupre, et al, 2019). For example, Ikanga et al, in press) tested a core assumption of the African Neuropsychology Battery (ANB), according to which greater African enculturation is associated with better performance on the ANB. The ANB assesses visuospatial perception, naming, memory, and abstract reasoning based on content drawn from sub-Saharan African cultures.…”
Section: Aims Of This Reviewmentioning
confidence: 99%
“…Although the participants were multilingual, language proficiency across languages was not formally assessed, and it is unlikely that participants were equally fluent across languages. Since participants were not administered multiple language versions of the measure, we were unable to conduct any analyses that examined cross-language comparisons (Ikanga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although the ANB has the potential to be used in the SSA countries, its applicability requires some caution across all SSA countries. As Ikanga et al (2022) have suggested, the SSA is not a “cultural monolith” and some memory items on ANB tests may not be culturally appropriate in each country in SSA. Therefore, national and regional adaptation to the ANB memory tests may be necessary to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…A second 12-word interference list is then presented after the third learning trial, followed by the short-delayed recall, and then a long-delay free recall trial approximately 20 minutes later. 39…”
Section: Methodsmentioning
confidence: 99%